A narrative review of the definition of 'flare' in hidradenitis suppurativa. (1st January 2020) - Kirby, J.S.; Moore, B.; Leiphart, P.; Shumaker, K.; Mammis‐Gierbolini, A.; Benhadou, F.; del Marmol, V.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory condition that can have periodic worsening or flares. Measurement of flare is important because it can inform treatment efficacy; however, it is unclear how HS flare should be defined. Objectives: This study reviewed the literature for definitions of HS flare. Methods: The PubMed MEDLINE online database was searched on 10 January 2018 and the search was repeated on 8 December 2018 for new publications. Titles and abstracts were screened for inclusion. Subsequently, full articles were screened for inclusion. Papers were included if the publication was a systematic review, clinical trial, cohort study, case report or series, or cross‐sectional study. Studies were excluded if they were journalistic reviews, did not discuss clinical findings of HS or did not use the words 'flare', 'exacerbation', 'relapse' or 'recurrence'. Results: Two hundred and seventy‐four papers were identified and 154 fulfilled the study criteria. Of these, 27 (17.5%) included the term 'flare' and 16 (10.4%) included the term 'exacerbation'. Two of the 27 papers (7%) defined the term flare and both included patient report of changes in symptoms or signs. One of 16 papers (6%) defined exacerbation, which was taken as one new HS lesion. The terms 'recurrence' and 'relapse' were more apt to be defined: 13% (13 of 100) and 14% (six of 44), respectively. Conclusions : The lack of a specific and measurable definition of HS flare is a barrier to assessment of this important outcome. Once a specific and measurable definition is established, validated and reliable measures of HS flare can be incorporated into future studies. What's already known about this topic? Hidradenitis suppurativa (HS) is a chronic, relapsing inflammatory skin condition. The ability to assess flares is important to people who have HS; however, it is unclear how this is defined. HS flare is one of the core outcomes in the core outcome set for HS clinical trials; however, it is unclear how this should be assessed. What does this study add? This literature review reveals the paucity of measurable definitions associated with the use of the term 'flare' in the HS literature. It also highlights the variation and lack of a validated and reliable measure of HS flare.